Hydroxychloroquine Protects against Cardiac Ischaemia/Reperfusion Injury In Vivo via Enhancement of ERK1/2 Phosphorylation. - Lauren Bourke; James McCormick; Valerie Taylor; Charis Pericleous; Benoit Blanchet; Nathalie Costedoat-Chalumeau; Daniel Stuckey; Mark F Lythgoe; Anastasis Stephanou; Yiannis Ioannou (PLoS ONE)
An increasing number of investigations including human studies demonstrate that pharmacological ischaemic preconditioning is a viable way to protect the heart from myocardial ischaemia/reperfusion (I/R) injury. This study investigated the role of hydroxychloroquine (HCQ) in the heart during I/R injury. In vitro and in vivo models of myocardial I/R injury were used to assess the effects of HCQ. It was found that HCQ was protective in neonatal rat cardiomyocytes through inhibition of apoptosis, measured by TUNEL and cleaved caspase-3. This protection in vitro was mediated through enhancement of ERK1/2 phosphorylation mediated by HCQ in a dose-dependent fashion. A decrease in infarct size was observed in an in vivo model of myocardial I/R injury in HCQ treated animals and furthermore this protection was blocked in the presence of the ERK1/2 inhibitor U0126. For the first time, we have shown that HCQ promotes a preconditioning like protection in an in vivo simulated rat myocardial I/R injury model. Moreover, it was shown that HCQ is protective via enhanced phosphorylation of the pro-survival kinase ERK1/2.